Spirituality and Cardiovascular Disease: A Bibliometric Analysis of Scopus (1999-2024) - Guerrero-Alcedo, Jesús (Journal of religion and health, 2026)
The relationship between spirituality and cardiovascular health has been the subject of growing interest in scientific literature; however, the evidence available still presents important gaps and a lack of clarity in relation to scope and impact. Currently, no study has explored bibliometric indicators of production, trend, collaboration and impact of this topic. Thus, we performed a bibliometric review in the Scopus database covering the period from 1999 to 2024. Taking into account the recommendations of the BIBLIO guide, 116 studies addressing this topic were identified. The annual growth rate was 4.66%, with the United States, the "Iran University of Medical Sciences", the "Journal of Religion and Health" and the author Ai Amy Lee leading the scientific production. Most of the documents reviewed were articles (76.72%), and the predominant language was English (96.55%). Likewise, the keyword co-occurrence network and co-authorship networks highlight the thematic interconnection in studies on spirituality, religiosity, cardiovascular diseases, heart failure and quality of life. The co-authorship network highlights the predominant collaboration between authors and countries, with Ai, Amy Lee, and the United States being of note. These findings contribute to mapping the current state of research on this topic, providing a solid foundation for future research, guiding investigators toward promising areas, as well as encouraging a more holistic, preventive, fair, and collaborative approach.